Ultrasound Imaging and Antithrombotic Effects of PLA-Combined Fe3O4-GO-ASA Multifunctional Nanobubbles - Zhang, Jie; Liu, Zheng; Chang, Cunyi; Hu, Ming; Teng, Yang; Li, Jinjing; Zhang, Xiangyu; Chi, Yanxia (Frontiers in Medicine, 2021)
PLA-combined ferroferric oxide–graphene oxide–aspirin (Fe3O4-GO-ASA) multifunctional nanobubbles were prepared using the double emulsion-solvent evaporation method. The obtained composite nanobubbles had a regular spherical shape, Zeta potential of (−36.5 ± 10.0) mV, and particle size distribution range of 200–700 nm. The experimental results showed that PLA-combined Fe3O4-GO-ASA nanobubbles could effectively improve the antithrombin parameters of PT, TT, APTT, and INR, and significantly inhibit thrombosis when the composite nanobubbles with a concentration of 80 mg·mL−1 interacted with the rabbit blood. The prepared composite nanobubbles could reach a significant ultrasonic imaging effect and good magnetic targeting under the magnetic field when the nanobubbles' concentration was only 60 mg·mL−1.